"دور تصنيف وقياس التكاليف البيئية في اتخاذ القرارات في القطاع الصحي" ( دراسة حالة على مشفى الباسل في طرطوس) - ديك, رولى; إبراهيم, علي; ليلا, بهاء (Latakia University Journal - Economic and Legal Sciences Series, 2017)
كنتيجة للاهتمام المتزايد بالموضوع البيئي, في البيئة السورية, وبشكل خاص بالقطاع الصحي الخدمي, وبسبب مواجهة أغلب المنشآت والشركات بمختلف قطاعاتها مشكلة قياس وتحليل التكاليف البيئية والإفصاح عن التكاليف البيئية في قوائمها المالية. هدف هذا البحث إلى استكشاف الدور الذي يلعبه قياس وتصنيف التكاليف البيئية في اتخاذ القرارات في القطاع الصحي.لتحقيق هدف البحث أجرت الباحثة دراسة حالة على إحدى المستشفيات في البيئة السورية في محافظة طرطوس, وهي الهيئة العامة لمشفى الباسل. إذ تم جمع البيانات اللازمة للدراسة من خلال الملاحظة وتحليل المستندات والتقارير العائدة للمشفى إلى جانب إجراء المقابلات الشخصية مع المديرين ورؤساء الأقسام والمحاسبين في المشفى.توصلت الدراسة إلى اقتراح نموذج لتصنيف التكاليف البيئية في المشفى المدروس وفقاً لنموذج Shapiro, أظهرت النتائج أنّ تكلفة الحيازة, تكلفة التوريد, التدريب والتأهيل, تكاليف التخزين, تكاليف الإزالة, تكاليف التخلص, تكاليف الصيانة تعدّ ملائمة لاتخاذ القرارات البيئية في المشفى. كما بينت الدراسة أنّ ضعف المعرفة والوعي لدى الكادر الإداري والمحاسبي بمفاهيم ومصطلحات المحاسبة البيئية, تؤثر سلباً في عملية تتبع وقياس التكاليف البيئية وبالتالي في جودة القرارات البيئية المتخذة. وكممارسات بيئية أظهرت النتائج أنّ المشفى يلتزم التزاماً شبه كامل بفرز وفصل النفايات الطبية وغير الطبية بكافة الشعب والأقسام.As a result of the growing interest in environmental issues in the Syrian environment, more precisely in the health service sector, companies in various sectors are facing the problem of measuring and analyzing environmental costs, and disclosing environmental costs in their financial statements. This research explores the role of measuring and classifying environmental costs in decision-making in the health sector.A case study was conducted in the General Authority of the Basel Hospital in Tartous in Syria. Data was collected using observations and analysis of hospital documents and reports, and personal interviews with managers and heads of departments and accountants in the hospital.The research aimed at finding a proposed model for classifying environmental costs in the hospital based on Shapiro's model. The results showed that the cost of acquisition, supply cost, training and qualification, storage costs, obsolescence costs, disposal costs, maintenance costs are considered appropriate to make environmental decision-making. The study also showed that the lack of knowledge and awareness of the administrative and accounting staff about concepts and terminology of environmental accounting adversely affect the process of tracking and measuring the environmental costs and hence the quality of environmental decisions. The results showed also that the hospital is almost committed completely to sort and separate medical and non-medical waste in all divisions and sections.